Photoinduced piezooptical changes caused by microsecond CO2 Infrared lasers in lead-germanate rare earth tridoped glasses - Pires Kassab, Luciana R.; Camilo, Mauricio Eiji; Ali Hussain, Reshak, Prof. Dr.; Plucinski, K. J. (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com/